Films that Gave Us Boldness: East European Documentaries Screened in Poland (1987-1993) as Refl ected in the Film Press of the Time - Hučková, Jadwiga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
“Films from East” signalling the political breakdown in the middle of the 1980s (the Gorbachev era) were welcom ed in the offi cial circulation system. Th e fi lms were screened not only in festival cinemas, but on TV as well, and were discussed in newspapers and magazines. Soviet fi lms were especially important because they were able to carry new information about the changes taking place in Eastern Europe. If independent ideas appeared in a Polish fi lm, it could be banned from screening, as censorship was sensitive to works “threatening socialism” and “disturbing the alliance”. Th e only country in our part of Europe which did not need to be afraid of “disturbing the alliance” was the Soviet Union. We can distinguish three groups of such documentaries: analyses of social life (for example: Is It Easy to be Young? by Yuris Podnieks, Borderline by Tatiana Skabard), fi lms about contemporary threats, provoked by the Chernobyl disaster (An Unpublished Album by Victor Kripchenko and Volodymyr Taranchenko, Chernobyl the Chronicle of Diffi cult Weeks by Volodymyr Shevchenko) and documentaries “squaring accounts” with history, fi lling in so-called “blank spots” (Termination of an Agreement by Murat Mamedov, Solovki Power by Marina Goldovskaya).